Seismic Risk Analysis for Critical Infrastructure: The Case Study of a Medical Center and its Supporting Systems in Yangon, Myanmar - Mon, Khin Aye; Kyaw, Kyaw; San, Zin Mar Lar Tin; Kiyono, Junji; Koike, Takeshi; Htet, Aung; Aye, Chit Nyein; Oo, Yin New (Institut Teknologi Sepuluh Nopember, 2017)
Myanmar has a great strike-slip active fault called the â€œSagaing Fault Zoneâ€ besides the Sumatra-Andaman Subduction Zone. Major cities (Yangon, Naypyitaw, Bago and Mandalay) are at risk along this fault. Recently, in 2012, Thabeikkyin earthquake with Magnitude of 6.8 caused collapse of many residential housings and ground failures near Mandalay. Therefore more attention should be paid for Yangon which has no large earthquakes since 1930 and is the largest not only in population but also in socio-economic activity. One of the most important concerns after an earthquake is to survive under any disastrous conditions. The medical care is requested not only for emergent injured people after an earthquake, but also for various types of patient and aged people from several weeks to longer periods. So medical center must be always functional before and after earthquake. For this purpose, medical buildings should be structurally resilient and also be functional for medical services by sustainable supply of electric power, water and any other delivery service which can be carried out by urban lifeline systems. This research is to investigate the structural vulnerability of hospital buildings and facilities, to assess the performance of urban lifeline systems and to check the operational capability of medical services in which surgical capability and life safety management method should be discussed. The water supply system is adopted as a typical lifeline system in Yangon in this study. One sample medical center in Yangon is adopted to carry out this analysis. Finally, the performance of medical services after the earthquakes can be assessed in a probabilistic manner.